Phytochemical and Biological Investigations of Bacopa monnieri L. (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Bacopa monnieri L. (Family: Scrophulariaceae), a medicinal herb of Bangladesh, has been used in traditional medicine to increase memory and brain power. The present research was aimed to investigate the phytochemical composition and biological activities of whole plant of B. monnieri. Through phytochemical analysis, two triterpenes, taraxerone and betulinic acid were obtained from B. monnieri. The crude methanol extract of the whole plant of Bacopa monnieri and its petroleum ether, dichloromethane, chloroform and aqueous fractions were screened for determination of several in vitro biological activities. In DPPH assay for antioxidant test, the dichloromethane fraction showed strong DPPH radical quenching activity (IC50 = 3.78 μg/ml). The chloroform fraction exhibited the maximum lethal concentration, LC50 value of 5.5 μg/ml against brine shrimp. In membrane stabilization assay, the crude extract and all solvent fractions revealed significant anti-inflammatory activity by inhibiting hemolysis of RBC induced by both hypotonic solution and heat. In thrombolytic assay, the petroleum ether fraction demonstrated highest thrombolytic activity (39.24%), when compared to the standard streptokinase (64.22%). In antimicrobial screening, the chloroform fraction displayed reasonable activity against most of the tested microorganisms. This study concludes that B.  monnieri has potential antioxidant, anti-inflammatory and thrombolytic activities.Dhaka Univ. J. Pharm. Sci. 22(2): 155-161, 2023 (December)